Calculations and prognosis of the influence of the exploitation of the "Hotyslavske" quarry on the hydrodinamics of the ground and underground waters of the Western Polissya - Diatel, Olexandr O. (КНУБА : ІТГІП, 2018)
The problems of the influence of the exploitation of the deposit of the sand and chalk "Khotislavske" on the hydrodynamics of ground and underground waters of Western Polissya are considered. At this the analytical methods of calculation of geophiltration processes and methods of mathematical modeling were used. The analysis of the validity of forecast calculations and modeling of the influence of a quarry on the territory of Ukraine carried out by the Belarusian side and the comparison of data are carried out.
Keywords: filtration area; infiltration recharge; water inflow; hydrogeological conditions; overdraining; technogenic conditions; 556.182; 631.621; 532.5; 519.86